Nurses’ job crafting, work engagement, and well-being: a path analysis - Sujeong Han (BMC Nursing, 2023)
Abstract Background Nurses’ well-being is a topic of interest at both individual and organizational levels. Studies that explore the relationship between nurses’ job crafting, work engagement, and well-being are scarce. Therefore, the purpose of this study was to confirm the effect of job crafting and work engagement on nurses’ well-being. Methods This cross-sectional survey study involved 207 nurses within a week in July 2022 across two centers, among whom the response rate was 99%. Three following instruments were used in the survey: the 14-item well-being scale, the 12-item job crafting scale, and the 9-item Utrecht Work Engagement Scores (UWES). Path analysis was performed and goodness of fit was evaluated. Results Job crafting and work engagement were strongly correlated with well-being, and nurses’ well-being was affected by job crafting and work engagement. Path model fit indices were adequate. The mediating effect of work engagement on the relationship between job crafting and well-being revealed that task job crafting influenced psychological well-being through work engagement (Effect: 0.15, 95% confidence interval [CI]: 0.08–0.22, p = 0.001). Furthermore, relational job crafting influenced social well-being through work engagement (Effect: 0.22, 95% CI: 0.11–0.38, p = 0.001). Conclusion The study’s findings can help strategize human resource management programs to enhance relational job crafting to improve nurses’ social well-being and enhance task job crafting to improve their psychological well-being. Furthermore, through job crafting, improved human resource policies can enhance work engagement and improve nurses’ well-being.